2017 Kansas Public Health Workforce Assessment Results - Timothy, Manges (My University, 2021)
Performing routine assessments of workforce proficiency is important for any field. The results from these assessments make it possible to identify and develop the specific education and training necessary for improvement. Workforce assessments are especially important for the field of public health since this workforce is responsible for providing essential public health services. The state of Kansas has conducted several public health workforce assessments; in 2003/2005, 2014, and most recently, in 2017. The Kansas assessments, executed by the Kansas Department of Health and Environment (KDHE), are accomplished by surveying the staff members of the KDHE and local health departments (LHDs). The survey determines workforce proficiency by asking participants to report a self-assessment of several public health core competencies. The 2017 assessment results show that the Kansas public health workforce is newer and younger than the 2014 workforce. Hence, educating, training, and retaining this workforce could be more crucial than ever before. The education and training needs for the Kansas workforce, determined by the 2017 assessment, are financial planning and management, public health science, and analytical/assessment skills. Two national public health workforce assessments were conducted in 2014 and 2017. The national assessments used surveys to determine workforce proficiency in a similar way to the Kansas surveys. Since both national and Kansas public health workforce assessments were completed in 2017, this report shares interesting results from the comparison of the two assessments. One of these comparison results is that the 2017 national assessment determined that budget and financial management is a top training need for the national public health workforce, which is also true for the Kansas workforce. Therefore, one of the recommendations from this report is to develop strategies providing education and training in financial planning and management to the Kansas public health workforce. New public health workforce assessments are scheduled to be conducted in 2020, both nationally and in Kansas. It will be interesting to determine if the recommendations from previous assessments were implemented and if they have improved the proficiency of the respective public health workforces. It is important for Kansas to continue improving the survey used for assessments. One recommendation from this report is to add more spatial components to the survey, so even more specific recommendations can be developed.
Keywords: Kansas; public health; workforce; core competencies; assessment; survey